pH-metric and Thermodynamic Studies on Metal Chelates of Al(III), Cr(III) and Fe(III) Ions with Tridentate Biprotic Ligands - Sharma, Anu; Mathur, R.P. (Asian Journal of Chemistry, 2010)
The pH-metric studies on the metal chelates of trivalent AI (III), Cr(III) and Fe(III) ions with the tridentate biprotic ligands derived from dibenzoylmethane with o-aminobenzoic acid- (H2BB) and 2-aminopropanoic acid (H2BP), respectively, have been carried out by employing Calvin-Bjerrum pH-titration technique at 25°, 35° and 45 ± 0.1 °C (μ= 0.01.0.05 and 0.1 M NaCIO4) in aqueous media The dissociation constants (pK1 and pK2), θo and pkmh value of the ligands have been evaluated. The stability constants have been determined and these values follow the Irving-William order. The thermodynamic parameters (ΔGo, ΔHo and ΔSo) of the chelation have been evaluated and discussed.